Tourism Governance and the Policy-Implementation Gap in Nepal: A Comparative Analysis of Institutional Failure - Pradhan, Asutosh (Nepalese Culture, 2026)
Despite Nepal having rich cultural and natural tourism assets and the existence of well-formulated national policies, the sector continues to underperform in terms of sustainability, inclusivity, and governance effectiveness. This paper critically examines why strong tourism policies in Nepal fail to translate into effective implementation outcomes. Drawing on governance theory, sustainable tourism frameworks, and cultural commodification theory, the study conceptualizes the Nepal tourism system as a fragmented governance structure characterized by weak institutional coordination, limited accountability, and a persistent policy–implementation gap. The paper further integrates comparative insights from Bhutan, Costa Rica, and the Maldives to demonstrate how governance quality, institutional coherence, and sustainability-oriented policy enforcement shape tourism success. The findings suggest that the Nepal tourism challenge is not a policy deficiency but a governance failure embedded in institutional fragmentation and weak implementation mechanisms. The study contributes to tourism governance literature by developing a multi-level implementation failure framework applicable to developing-country tourism systems. Through systematic comparison with Bhutan's regulatory model, Costa Rica's certification system, and the Maldives' PPP framework, the analysis identifies specific transferable governance instruments that could operationalize Nepal's existing policy provisions.